Fine‐scale diversity and distribution of ectomycorrhizal fungal mycelium in a Scots pine forest. Issue 4 (18th December 2013) - Anderson, Ian C.; Genney, David R.; Alexander, Ian J.
Summary: Ectomycorrhizal (ECM) mycelium is a key component of the ectomycorrhizal symbiosis, yet we know little regarding the fine‐scale diversity and distribution of mycelium in ECM fungal communities. We collected four 20 × 20 × 2‐cm 3 (800‐cm 3 ) slices of Scots pine ( Pinus sylvestris ) forest soil and divided each into 100 2 × 2 × 2‐cm 3 (8‐cm 3 ) cubes. The presence of mycelium of ECM fungi was determined using an internal transcribed spacer (ITS) database terminal restriction fragment length polymorphism (T‐RFLP) approach. As expected, many more ECM fungi were detected as mycelium than as ectomycorrhizas in a cube or slice. More surprisingly, up to one‐quarter of the 43 species previously detected as ectomycorrhizas over an area of 400 m 2 could be detected in a single 8‐cm 3 cube, and up to three‐quarters in a single 800‐cm 3 slice. ECM mycelium frequency decreased markedly with depth and there were distinct 'hotspots' of mycelium in the moss/F1 layer. Our data demonstrate a high diversity of ECM mycelium in a small (8‐cm 3 ) volume of substrate, and indicate that the spatial scale at which ECM species are distributed as mycelium may be very different from the spatial scale at which they are distributed as tips. Abstract : See also the Commentary by Dickie and Koide